Improving Education Quality through Contingent Leadership and Cadre System - Fitriana, Aiza; Prasetyo, Muhammad Anggung Manumanoso (Tsaqofah : Jurnal Pendidikan Islam, 2023)
This research aims to examine how to improve the quality of contingent leadership through the regeneration system and the model of the leadership relationship with the regeneration system. This research is a type of library research, using qualitative method. The results show that contingent leadership is a leadership model that is considered effective because it adapts to the situation. The model of the leadership relationship and the regeneration system the relationship between the characteristics of the leader, the internal and external environment, the characteristics of members / subordinates, leader behavior and style, effective leadership and regeneration.